2022
DOI: 10.1136/bmjopen-2021-054690
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on patients with paediatric cancer in low-income, middle-income and high-income countries: a multicentre, international, observational cohort study

Abstract: ObjectivesPaediatric cancer is a leading cause of death for children. Children in low-income and middle-income countries (LMICs) were four times more likely to die than children in high-income countries (HICs). This study aimed to test the hypothesis that the COVID-19 pandemic had affected the delivery of healthcare services worldwide, and exacerbated the disparity in paediatric cancer outcomes between LMICs and HICs.DesignA multicentre, international, collaborative cohort study.Setting91 hospitals and cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…42 However, it has been shown that there is a difference between high income countries and low and middle income countries regarding COVID-19-related delay in treatment. 28 We showed that generally, treatment (including surgery) according to the UMBRELLA protocol was feasible without much delay. Previous studies reported shortage of staff and healthcare facilities as a reason for delay in management of patients with cancer.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…42 However, it has been shown that there is a difference between high income countries and low and middle income countries regarding COVID-19-related delay in treatment. 28 We showed that generally, treatment (including surgery) according to the UMBRELLA protocol was feasible without much delay. Previous studies reported shortage of staff and healthcare facilities as a reason for delay in management of patients with cancer.…”
Section: Discussionmentioning
confidence: 89%
“…[26][27][28] The latter was especially the case in low and middle income countries, where delay and shortage of material and personnel played a larger role than in high income countries. 28 The aforementioned reports reflect mostly either adult cancer and/or national cancer registry perspectives. Therefore, the possibility to ascertain the impact on individual cancer types and organisation of care for subsets of patients on a global scale is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Study centers were distributed throughout the continents, with several involving international multicenter and conducted by collaborating authors. 1 , 10 , 11 We provide geographical distribution of studies included in this review ( Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Mainly through delay of treatment and centralization of resources, the pandemic have impacted the already-poor outcome of cancer patients especially in low-middle income countries and up to fifteen-fold worsened mortality rate compared to the pre-pandemic data. 11 Regulations and policies made by the higher-ups of contributing sectors within a country should take into account the burden of co-morbidities and other diseases that may concur with sarcoma. 1 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation